Convergence Over Time or Not? U.S. Wages by Sexual Orientation, 2001-2018 - Christopher Jepsen; Lisa Jepsen (Institute of Labor Economics (IZA), 2020)
An extensive literature on labor-market outcomes by sexual orientation finds lower wages for gay men compared to heterosexual men and higher wages for lesbians compared to heterosexual women. Recent work looking over multiple time periods provides suggestive evidence, however, that the wage penalty for gay men is heading toward zero. Using data from the American Community Survey on individuals in couples from the 2001 to 2018, we find that the annual wage/salary penalty for gay men is stable since 2008. Although the annual wage/salary premium for lesbians declines slightly, convergence to heterosexual female earnings at the current rate would not occur for at least 15 years. The persistence of a wage penalty for gay men in the face of anti-discrimination policies and rising overall tolerance by Americans is concerning.
Keywords: D10; J10; J12; J70; 330; wages; employment; sexual orientation; discrimination